(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical characteristics and management methods for sexual dysfunction in perimenopausal and postmenopausal women. Subjects and methods: From July 2024 to April 2026, 25 cases of sexual dysfunction in perimenopausal and menopausal women were recorded at the Hanoi Center for Sexual Medicine. All patients underwent clinical evaluation for menopausal symptoms, characteristics of sexual activity, and morphological types of sexual dysfunction. Screening and assessments were conducted using the menopause rating scale (MRS), decreased sexual desire screener (DSDS), female sexual function index (FSFI), and female sexual distress scale-revised (FSDS-R). Treatment modalities were also documented. Results: The study subjects had a mean age of 47.5 ± 6.1. The majority (52%) reported being “very dissatisfied” or “somewhat dissatisfied” with their sex lives. The most frequently observed disorder was hypoactive sexual desire (96%), followed by dyspareunia (pain during intercourse) (68%). The mean duration of the condition was 2.4 years, and 76% of patients presented with 2 or more concurrent dysfunctions. The mean MRS score was 16.56 ± 6.27, with severe (32%) and very severe (56%) cases comprising the majority. The mean FSFI score was 19.22, and 64% of patients exhibited psychological distress associated with sexual dysfunction as screened by the FSDS-R scale. Pharmacological treatments alongside counseling and education were implemented for all patients. Specifically, hormone therapy was administered in 22 cases, whereas lubricating gels and vaginal moisturizers were utilized in 11 and 15 cases, respectively. Pelvic floor physical therapy was prescribed for 6 patients, and mindfulness-based therapy was applied in 5 cases. Conclusion: Female sexual dysfunction during menopause presents as a complex, chronic condition frequently characterized by a combination of multiple symptoms-most notably, hypoactive sexual desire and dyspareunia-resulting in profound negative impacts on psychological well-being and overall quality of life. Consequently, therapeutic strategies mandate a multidisciplinary approach: establishing counseling and education as foundational elements, while integrating personalized hormone therapy, localized topical treatments, and physical/psychological support to comprehensively address the patients’ conditions.